2020
DOI: 10.1177/0165551520977447
|View full text |Cite
|
Sign up to set email alerts
|

A spike in the scientific output on social sciences in Vietnam for recent three years: Evidence from bibliometric analysis in Scopus database (2000–2019)

Abstract: Bibliometric analysis of 3105 publications retrieved from the Scopus database was conducted to evaluate bibliographic content of scientific output on social sciences in Vietnam, for the 2000–2019 period. Our main findings show that the number of publications on social sciences from Vietnam has increased significantly over the last two decades, and there was a spike in the scientific output for the recent three years when the number of publications accounted for 53.76% of the collection. The most productive aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…Similar to those in previous analyses, findings in this study showed that despite a gradual decline in recent years, the contribution of international collaborations to the total number of publications is huge (through the position of the first author, corresponding authors, and fundings) [ 7 , 22 , 23 ]. This is especially true in empirical research fields, which require great investment in equipment and technology as well as technology transfer activities from countries with more advanced science.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to those in previous analyses, findings in this study showed that despite a gradual decline in recent years, the contribution of international collaborations to the total number of publications is huge (through the position of the first author, corresponding authors, and fundings) [ 7 , 22 , 23 ]. This is especially true in empirical research fields, which require great investment in equipment and technology as well as technology transfer activities from countries with more advanced science.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the cooperation network between strong research centers and local research units should be strongly encouraged to improve the scientific productivity and scientific research capacity of research institutions in these less developed regions. Similar to those in previous analyses, findings in this study showed that despite a gradual decline in recent years, the contribution of international collaborations to the total number of publications is huge (through the position of the first author, corresponding authors, and fundings) [7,22,23]. This is especially true in empirical research fields, which require great investment in equipment and technology as well as technology transfer activities from countries with more advanced science.…”
Section: Principal Findingssupporting
confidence: 86%
See 2 more Smart Citations
“…This method was then extended by Heck and Bremser (Heck & Bremser, 1986), by adding author and institute analyses. This type of bibliometric analysis has been widely used to analyse scientific evolution of various research fields at global and local scales such as, in medicine (Tran et al, 2018; Tran, Vu, et al, 2019), remote sensing (Pham‐Duc, Nguyen, et al, 2020; Zhang et al, 2017), higher education (Hallinger & Chatpinyakoop, 2019), energy research (Chen et al, 2016), tsunami research (Chiu & Ho, 2007), sustainable tourism (Della Corte et al, 2019), management and organization (Zupic & Čater, 2015), terahertz research (Li et al, 2020), social sciences (Pham‐Duc, Tran, et al, 2020) or event‐based control (Aranda‐Escolastico et al, 2020). Bibliometric analysis of Industry 4.0 has been studied in several papers, but mostly focused on evaluation the global research trend (Cobo et al, 2018; Janik & Ryszko, 2018; Kipper et al, 2020; Mariani & Borghi, 2019; Muhuri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%